PENGARUH WARNA WADAH TERHADAP KECEEARAHAN WARNA IKAN CUPANG (BETTA SP.) - MOH. IKROM; HAMID HAMID; AMINULLAH AMINULLAH (GANEC SWARA, 2024)
Ornamental fish are a fishery commodity that has high economic value because of their attractive pattern, shape and color, especially freshwater ornamental fish. Betta fish (Betta sp.) is a type of ornamental fish that is very popular among Indonesian people, from children to adults because it does not require difficult care. One of the main attractions of betta fish is their unique fin shape and color pattern. This research aims to describe the effect of the color of the container on the brightness of the color of Betta fish (Betta sp.). This research is a type of experimental research that uses a Completely Randomized Design (CRD). Data collection uses observation and documentation techniques. This research used 4 different container treatments, namely: A: clear container, B: black container, C: blue container, and D: red container. Primary data collected included: (1) Changes in the brightness of the color of the betta fish, (2). Fish survival rate, and (3) Water quality parameters (temperature, pH, DO, ammonia). The observation results showed that treatment C (blue container) gave the highest increase in color brightness for betta fish, namely 2.25. Meanwhile, the lowest brightness value was found in treatment A (clear) = 0.75. However, the results of the Anova test showed that the use of different container colors did not have a real effect on increasing the brightness of the color of the betta fish